Influence of estrogen exposure on systemic lupus erythematosus in Bangladeshi women: a case-control study scenario - Sabrina Jabeen; Meerjady Sabrina Flora; Ashraf Ur Rahman (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study was conducted to find out the association between estrogen exposure and systemic lupus erythematosus (SLE) in Bangladeshi women. Design/methodology/approach - A case-control study was carried out from January to December 2015 among 128 intervention cases and 128 age-matched control group participants to find out the association with estrogen exposure and development of SLE. Findings - Case group participants were five times (OR 5.14, 95% CI 2.14-12.33), three times (OR 3.40, 95% CI 1.25-9.21) and four times (OR 4.00, 95% CI 1.45-11.00) more likely to receive different higher levels of education compared to the control group. Exposure to estrogen showed a positive association with the development of SLE. The case group (12.63 ± 1.61 years) had a lower age at menarche than that of the control group (13.31 ± 1.47 years; p < 0.001) and their proportion (62.6%) of using oral contraceptive pills were more than that of the control group (45.6%; p < 0.01). After controlling the effect of the positively associated variables, SLE patients were found two times (adjusted OR 2.26; 95% CI 1.29-3.95) more likely to use oral contraceptive pills than the control group. The case group was more (adjusted OR 0.771; 95% CI 0.642-0.927) prone to have an earlier age at menarche compared to the control group. Originality/value - This study identified the association between estrogen exposure and SLE. Contraceptive pills should be used cautiously and both consumers and service providers need to be aware of their effects.